Synergistic efficacy of three plant extracts, bergeniaciliata, acoruscalamus and dioscoreabulbifera for antimicrobial activity - K. GOWRI SHANKAR; ALBIN T FLEMING; R.VIDHYA; NAMRATA PRADHAN (International Journal of Pharma and Bio Sciences, 2016)
To evaluate the synergistic potency of three different plants namely rhizome of Bergenia ciliata, Acorus calamus and tuber of Dioscorea bulbifera in exhibiting the antibacterial activity, phytochemical evaluation and molecular docking analysis. 5mg/ml, Sample II and III acetone extract of plant mixture containing A. calamus, B. ciliata and D. bulbifera in the ratio 1:2:1 and 1:1:2 against E. coli, showed 12mm and 13mm, P. aeruginosa showed 13mm and 16mm and B. subtilis showed 23mm and 18mm zone of inhibition. To identify, the chemical compounds responsible for antimicrobial activity the acetone extract of sample II and III which was analysed using GC-MS and Molecular Docking. Compared to other metabolites alpha.- (N,N-Dimethylamino)-3’-hydroxy-4’-methoxyacetophenone and Cis-Asarone are most potent metabolites which has lowest docking score against the receptors at various degrees. The results will be useful for further design of novel cancer and microbial inhibitors derived from synergistic plant extract.